Civil substantive and procedural legal means of securing reparations for Ukraine - O. G. Bortnik (Bulletin of Kharkiv National University of Internal Affairs)
The subject of the study is the forms of reparations for damage and the procedural means of obtaining them within the institutions which constitute transitional justice and which should comply with international standards. The purpose of the article is to determine the directions for institutional changes in the procedure and peculiarities of compensation for damage caused to individuals by the armed aggression of the russian federation, primarily in national courts in the context of legal institutions of transitional justice. To obtain the results of the study, the author used general scientific and special legal methods, in particular, analysis, generalisation, and comparative legal analysis.